"Thinking about drinking tea but not drinking tea": Pre-service English teacher education during the COVID-19 pandemic in Turkish EFL context. (11th May 2023) - Atmaca, Çağla
This phenomenological research aimed to investigate the reflections of 34 pre-service English teachers and 31 lecturers on distance education during the COVID-19 pandemic in Turkey. An online interview form was employed as data collection tool. The participants were sent the online form to collect their reflections on their online learning/teaching experiences during the pandemic. These reflections were analysed using phenomenological research steps. At the end of the analyses, distance education was found to be useful for improving the participants' technological literacy skills and delivering theoretical courses. However, it was found to be inappropriate for practical courses such as teaching practicum and community service practices. Furthermore, the participants used various metaphors to define their online teaching/learning experiences like emergency exit, one-sided mirror, frozen lake, growing in a cage, driving a car, and sky. The participants mostly did not receive any training before using the online platform. In light of the findings, it can be claimed that necessary arrangements should be made to improve the quality of online learning platforms and both pre-service English teachers and their lecturers should receive training to benefit from distance education more effectively. In this way, pre-service English teachers can be better prepared for their future teaching in case of distance education.